“LIFE OF THE STORK…” - Nuran ÖZLÜK (Fırat University, 2019)
Bringing on the speeches and images of dead or alive figures who are renowned and competent in their own fields for the purpose of humor, satire and criticism -which is one of the popular culture elements that often comes up in the present day social media accounts- existed long before in our journals and newspapers. In Seçilmiş Hikâyeler Journal, being one of these publications which came into press life only by publishing story but in time gave place to other genre as well, we encounter “Life of the Stork…” with subheading "Anecdotes/Jokes" which was written for the same purpose. One of the most important features of these pages is, on a regular basis during 18 issues between January 1956 and July 1957, there has been references to latest developments in cultural life of the period; the characteristic features and weaknesses of artists, journalists, movie makers/actor/actress, poets and authors like Nurullah Ataç, Attilâ İlhan, Fazıl Hüsnü Dağlarca, Tarık Buğra, Edip Cansever, Yaşar Kemal, Orhan Kemal, Cevat Şakir Kabaağaçlı, Metin Eloğlu, Tahsin Yücel, Ahmet Muhip Dıranas, Ümit Yaşar Oğuzcan, Can Yücel, İlhan Berk, Metin Eloğlu, Haldun Taner, Necati Cumalı, Nezihe Meriç, Muzaffer Erdost, Munis Faik Ozansoy, Vüsat O. Bener, Behçet Necatigil, Erdal Öz, Asaf Hâlet Çelebi, Orhan Duru, Yaşar Nabi Nayır, İlhan Tarsus, Tarık Dursun K., Vedat Günyol, Salim Şengil, M. Sunullah Arısoy, Yılmaz Gruda, Özdemir Âsaf, Şerif Hulusi, Şahap Sıtkı, Nevzat Üstün, Hüsamettin Bozok, Semih Tuğrul, Seyfettin Turhan, Adnan Benk, Ziya Metin, Cüneyt Gökçer, Şakir Sırmalı, Bedri Rahmi Eyüboğlu, Fikret Otyam with repartee, misconception, wordplays and ridicules using the signature of One of Us.